2022
DOI: 10.1038/s41598-022-19733-0
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration after partial hepatectomy is improved in the absence of aryl hydrocarbon receptor

Abstract: The liver is among the few organs having the ability to self-regenerate in response to a severe damage compromising its functionality. The Aryl hydrocarbon receptor (Ahr) is a transcription factor relevant for the detoxification of xenobiotics but also largely important for liver development and homeostasis. Hence, liver cell differentiation is developmentally modulated by Ahr through the controlled expression of pluripotency and stemness-inducing genes. Here, 2/3 partial hepatectomy (PH) was used as a clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…14,41,42 In addition, regeneration of the liver after PH improves in the absence of AhR. 43 The transient inhibition of AhR may improve liver regeneration in patients with liver resection and transplant. In this study, AhR had been involved in cell proliferation and the induction of inflammatory cytokines, tumor necrosis factor-alpha (TNFα), and interleukin (IL)-6 in the early phase after PH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,41,42 In addition, regeneration of the liver after PH improves in the absence of AhR. 43 The transient inhibition of AhR may improve liver regeneration in patients with liver resection and transplant. In this study, AhR had been involved in cell proliferation and the induction of inflammatory cytokines, tumor necrosis factor-alpha (TNFα), and interleukin (IL)-6 in the early phase after PH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have demonstrated compelling data to support the vital role of AhR signaling in innate immunity 14,41,42 . In addition, regeneration of the liver after PH improves in the absence of AhR 43 . The transient inhibition of AhR may improve liver regeneration in patients with liver resection and transplant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact is supported by previous studies that show that AHR prevents mitotic progression and induces differentiation, as well as preventing pluripotency in different cell types [ 28 , 30 , 126 , 127 , 128 ]. Moreover, several groups of genes involved in cell differentiation and development are regulated directly by AHR in the absence of an exogenous ligand [ 129 , 130 ].…”
Section: Ahr Physiological Functionsmentioning
confidence: 99%